Zinc and Coronavirus: Related Health Problems - Rami Allo; Rifaie Yaseen; Dorsaf Zellama (Wolters Kluwer Medknow Publications, 2024)
Background and Objectives: Zinc is an essential trace mineral required by the human body in minute quantities. It plays a crucial role in facilitating around 100 enzymes to perform key chemical reactions. It has a significant role in DNA synthesis, cellular proliferation, protein synthesis, tissue regeneration, and bolstering the immune system. Zinc toxicity primarily arises from the consumption of zinc supplements rather than from dietary sources. The study aimed to evaluate the side effects caused by the misuse of zinc during and after recovery from the coronavirus. Materials and Methods: A case series study design was used to carry out the study. The constructed checklist was applied to 107 patients who recovered from corona disease to determine the causes of the adverse health consequences they still suffer from after recovery, also, they underwent comprehensive laboratory tests in January 2023. Results: Nearby 50% of the study sample had zinc tests higher than the normal range, whereas they were suffering from such physical health disorders that were significantly enhanced due to management undertaken. Conclusions: The misuse of zinc tablets for a long time and in large doses caused such physical problems to be continued for a time among many patients recovering from coronavirus, and when the intake of zinc tablets and multivitamins supplements was stopped for 6 months an obvious improvement in these health symptoms occurred.